Application Of Information Search Model For Students Through Social Media - Hedi Heryadi; Hana Silvana (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
The purpose of this study was to obtain an overview of the application of information search models used by students in Bandung. The informants who participated were students at secondary schools. Eighteen students were selected as informants from each school. The schools selected for the study were SMPN 15, SMPN 29, SMPN 40, SMAN 15, SMA Sumatra 40, and SMA Kartika XIX-2. A qualitative research approach was used, with a case study method and purposive sampling. The results of the study show that, in general, the stages used in searching for information are carried out in three major stages, namely Starting, planning by organizing the steps in searching for information, and determining the subject to be used in searching for information. Analyzing, selecting the information to be used, analyzing the information obtained, storing unnecessary information, and using the necessary information. Evaluating, at this stage, students know when the information will be presented again, and the presentation of information is adjusted to the tasks and needs. On average, students search for information through the internet using Google search or social media. The information sought is mostly related to school assignments. This research advances this field by revealing patterned deviations from Ellis' model related to digital literacy levels.